Analisis Pelayanan Administrasi Kantor Camat Batipuh Kabupaten Tanah Datar - Nusantara, Kukuh (UIN Mahmud Yunus Batusangkar, 2024)
The main problems in this thesis are officers who lack discipline, officers who are less friendly and officers who lack insight in providing services to the community. The purpose of this discussion is to determine the quality of service that occurs at the Batipuh District office, Tanah Datar Regency. The type of research that the author uses is qualitative descriptive research, to obtain data from the problems studied. The data collection techniques used were observation, interviews and documentation. Data processing is carried out descriptively, then the aspects of certain problems are described and classified and explained in effective sentences. Based on the research results, it can be concluded that the efficiency principle put forward by AG. Subarsono has not been implemented properly by the Batipuh District Head's office. This can be seen from officers' delays in starting the service process and officers' lack of understanding in providing administrative information to the public. However, the service meets the time standards set by providing one active admin officer and there are no costs for carrying out the service process. The principle of responsiveness has also not been implemented well, as can be seen from officers using high-pitched voices when giving directions to the public. However, the Batipuh sub-district office also provides a suggestion box as a forum for input, criticism and aspirations from the community. Based on non-partisan principles, the Batipuh Subdistrict Office also strives to provide special routes for people with disabilities to make it easier and more comfortable for people with disabilities to provide services. However, in its implementation, the Batipuh District office also experienced problems, namely sudden power outages and poor network.